The Protection of Civilians and Protection of Peacekeeping Mandates: Gender and Ethics in Collective Security - Heathcote, Gina (feminists@law, 2016)
This lecture considers how Security Council authority and legitimacy gain traction through the deployment and development of normative provisions. I focus on the robust peacekeeping mandates in the UN Security Council Resolutions on the Protection of Civilians and on Women, Peace and Security to demonstrate how the Security Council's thematic resolutions are increasingly used to justify new modes of force. This raises questions regarding the ethics of a feminist project focused on supporting the women, peace and security framework that is increasingly co-opted into militarised peacekeeping. At the same time the Council's use of gender perspectives and the protection of civilians narrative is seemingly used to avoid scrutiny of its agenda and mandates, suggesting that the development of normative and thematic work requires greater scrutiny from critical and feminist actors.